Discourse Markers Used by Non-Native Speakers in Good Morning America Talk Show - Annisa, Annisa; Emmiyati, Nuri; Barsihannor (Elite : English and Literature Journal, 2023)
Discourse markers have been studied extensively in linguistics and communication studies. Its use is very helpful in understanding the message conveyed, both in formal and informal situations. This study examines the discourse markers used by non-native speakers in Good Morning America Talk Show. Unveil the types and their functions, this study uses a qualitative descriptive method in identifying the use of discourse markers. The data were taken from conversations of non-native speakers using Biber et al (1999) theory to determine the types and functions of discourse markers. The results of this study showed that there are ten types of discourse markers interjection, greetings and farewells, linking adverbials, stance adverbials, vocatives, response elicitors, response forms, hesitators, various polite speech-act formulas and expletives. Those markers have variations functions as marker of information management, marker of response, marker of connectives, marker of cause and effect, marker of temporal adverb and marker of information participation. This study has shown that the use of discourse markers varies across languages and cultures. Moreover, the use of discourse markers can also vary depending on the context of the communication.